2016
DOI: 10.36251/josi.109
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Attitudes to Universal Design in Architecture Education

Abstract: It is widely recognised that the built environment can dramatically impact on the participation and engagement of people with disability and diverse needs. It has therefore become necessary for architects and designers to consider these needs when working within their profession. The implementation of universal design teaching into architecture and design curriculum has been recognised as an important step in facilitating and enhancing the uptake of universal design during the design process. Using a quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…According to Larkin et al (2016), "the implementation of universal design teaching into Architecture and Design curriculum has been recognised as an important step in facilitating and enhancing the uptake of universal design during the design process" (p. 1). Nevertheless, the present study points to various gaps identified in different countries, suggesting a need for developing training tools and materials on D4All Dantas, Louceiro, Dias, Rodrigues, Moreira, Kotradyova, Čerešňová, Kacej, Filová, Šimková, Sánchez, Voľanská, Lutherová, Lipovac, Sašek, Šarabon and Podrekar, 2023 throughout Europe.…”
Section: Discussionmentioning
confidence: 99%
“…According to Larkin et al (2016), "the implementation of universal design teaching into Architecture and Design curriculum has been recognised as an important step in facilitating and enhancing the uptake of universal design during the design process" (p. 1). Nevertheless, the present study points to various gaps identified in different countries, suggesting a need for developing training tools and materials on D4All Dantas, Louceiro, Dias, Rodrigues, Moreira, Kotradyova, Čerešňová, Kacej, Filová, Šimková, Sánchez, Voľanská, Lutherová, Lipovac, Sašek, Šarabon and Podrekar, 2023 throughout Europe.…”
Section: Discussionmentioning
confidence: 99%